A critical review on effort estimation techniques for service-oriented-architecture-based applications. Issue 4 (1st October 2016) - Siddiqui, Zeeshan Ali; Tyagi, Kirti
Abstract: In the recent past, Service Oriented Architecture (SOA) has become very popular as it allows legacy systems to remain mostly unchanged and provide functionalities in the form of services. In contrast to traditional software application development, complexity of SOA application is much higher, making the effort estimation very difficult. Hence, existing effort estimation techniques and approaches are inadequate to address the complex SOA systems. In this literature review, distinct research directions for SOA-specific effort estimation are critically examined with the help of proposed review framework with nine point agenda that include the class, structure, purview, objective, technique, value added, flip side, inference, limitations, and future research scope. In the planning phase of a software project, estimating the effort is very critical and crucial to manage the risk of cost blowout happened during the development. Not much research has been available on effort estimation for SOA applications. However, there are some good frameworks and methods provided by researchers that make a solid foundation of effort estimation for SOA applications. Available effort estimation techniques for SOA applications are analyzed by critically examining their upside and flip-side.